2022
DOI: 10.3390/app12052735
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Tangent Stiffness of Train–Track–Bridge Systems Based on Artificial Neural Network

Abstract: Dynamic response analysis of a train–track–bridge (TTB) system is a challenging task for researchers and engineers, partially due to the complicated nature of the wheel–rail interaction (WRI). When Newton’s method is used to solve implicit nonlinear finite element equations of a TTB system, consistent tangent stiffness (CTS) is essential to guarantee the quadratic convergence rate. However, the derivation and software implementation of CTS for the WRI element require significant efforts. Artificial neural netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, in the general scope, it is hard to calculate the exact consistent tangent of an implicit and complicated network. A surrogate tangent can be learned with another ANN [ 44 , 45 ] from the data of the deformation gradient and the tangent calculated with DBFFT. One difficulty of this approach is that the tangent data is not always available.…”
Section: Applications Of the Single-point Calculatormentioning
confidence: 99%
“…However, in the general scope, it is hard to calculate the exact consistent tangent of an implicit and complicated network. A surrogate tangent can be learned with another ANN [ 44 , 45 ] from the data of the deformation gradient and the tangent calculated with DBFFT. One difficulty of this approach is that the tangent data is not always available.…”
Section: Applications Of the Single-point Calculatormentioning
confidence: 99%
“…Compared to other man-made structures, it can be observed that a railway track operates under unique conditions. This is due to the accumulation of local plastic deformations in all its elements [1][2][3][4][5]. This study aims to present the discourse on the reconceptualization of an integrated approach to the assessment of the change in the technical condition of a railway track under the action of rolling stock throughout its useful life, which is highly important in efforts to ensure the functional safety of the railway track.…”
Section: Introductionmentioning
confidence: 99%